The Power of Word-of-Mouth: Understanding the Dynamics of Organic Marketing in Faith-Based Educational Institutions - Muhammad Durrin Ni’am; Rifka Jannatul Firdausiyah; Moh Kamil; Siti Nur Aviatun Hasanah; Moh Rofik; Annisa Tri Ananda Dewi; Ittaqillah Haitsuma Kunta; Abu Hasan Agus R (Universitas Nurul Jadid, 2025)
This study analyzes how word-of-mouth (WOM) is used as an organic marketing strategy in faith-based educational institutions, especially its influence on the perception and decisions of prospective students. The research was conducted by quantitative surveys, collecting data from active students, alumni, and parents through structured questionnaires and supporting documents from institutions. The results show that the positive experiences of students, the credibility of mentors and teachers, and recommendations from senior students and alumni greatly influence the decision of prospective students. Data analysis showed positive experiences contributed the most, followed by the credibility of sources and peer recommendations. This confirms that direct interaction is more influential than formal promotion. Digital media is only an additional channel of information, while interpersonal interaction remains a major factor in the effectiveness of WOM. This study concludes that WOM in faith-based educational institutions runs through social interaction and trusted personal networks, thus becoming an effective and efficient marketing strategy. The implication of this research is that institutional managers can improve their reputation and attract prospective students by creating positive experiences, strengthening the role of mentors and seniors, and documenting original testimonials to optimize organic marketing strategies.